On the Synchronization of a Novel Fractional Order Chaotic System Using Nonlinear Control Method - Vishal, Kumar; Agrawal, Saurabh Kumar; Kumar, Lokesh (Discontinuity, Nonlinearity, and Complexity, 2026)
The present article studies chaos synchronization of a novel chaotic systems using nonlinear control method. Stability of system at equilibrium points are also discussed in brief for fractional order system. We use the nonlinear control method for synchronization between fractional order 3 scroll Dadras chaotic system with fractional order 2 scroll Lorenz and Chen chaotic systems. A nonlinear controller is designed for synchronization. Based on the design, the synchronization of considered chaotic systems is achieved only by using one controller. Nonlinear control method is a practicable method to synchronize chaotic systems. Adams-Boshforth-Moulton method is used for the computer simulation for integer order as well as fractional order in the Caputo sense. Graphical Results are also displayed to validate the effectiveness of the proposed method.